A novel and alternative treatment method for moderate diabetic foot ulcer: tibial periosteal distraction - Yusong Yuan; Xiaofang Ding; Hao Lu; Ying Chen; Hailin Xu (Journal of Orthopaedic Surgery and Research)
Abstract Objective Researchers have proposed a novel surgical treatment for moderate diabetic foot ulcer: tibial periosteal distraction (TPD) which could improve affected limb microcirculation. We aimed to describe the method and therapeutic effects of this technique. Methods We provided a technical guide to perform TPD surgery for the treatment of moderate diabetic foot ulcer of who had been treated in our department. The demographic information had been collected at the time of their admission. The patients were followed up at 3, 6, and 12 months after the operation with the ulcer area, skin temperature of the medial malleolus, transcutaneous oxygen pressure of the medial malleolus, ankle brachial index, dorsalis pedis artery pulsation, 12 item short form survey quality of life scale score, and visual analogue scale. Results A total of 35 patients with type 2 diabetes were included in this study, including 19 males and 16 females, with an average age of 62.49 ± 10.34 years and a maximum age of 87 years. The ulcers of all patients were cured, and the average healing time of ulcers was 8.09 ± 2.28 weeks, with no associated complications. The microcirculation indexes of the affected foot were significantly improved (p < 0.05). Three cases showed new vessels regeneration in the affected limbs according to their computed tomography angiography (CTA) results. Conclusion TPD surgery technique is a simple procedure that significantly increases the efficacy and reduces the complications of moderate diabetic foot ulcer patients, which could accelerate the formation of collateral circulation.